Beyond ‘equitable partnerships’: the imperative of transformative research collaborations with Africa - Aboderin Isabella; Fuh Divine; Balcha Gebremariam Eyob; Segalo Puleng (Global Social Challenges Journal, 2023)
Debate on the need for more fairness in academic research collaborations between actors in Africa (or the ‘Global South’, broadly) and counterparts in the Global North has intensified in recent years, while practice-oriented frameworks and efforts to foster more equitable partnerships have proliferated. Important approaches to recognise and undo asymmetries in concrete collaboration arrangements – division of labour, decision making, access to rewards, capacity building – have been identified. In this provocation we draw on African and other postcolonial, decolonial and feminist scholarship, as well as systems thinking and global science data to argue that such ‘equitable partnerships’ efforts at best sidestep the urgent need for a much more profound rebalancing of the positioning of Africa and ‘Global North’ in the worldwide science and research ecosystem as a whole. We consider why such wider rebalancing is an imperative for both Africa and the global community, propose that research collaborations must be understood as a key entry point for advancing such a systemic shift, and suggest a necessary transformative collaboration mode to this end. We conclude by positing an urgent need to think and act beyond ‘equitable’ partnerships and highlight where responsibilities for action must lie.